Storage Stability of Fish Waste Peptone at Ambient Temperature - Achmad Poernomo; Farida Ariyani; Murdinah Murdinah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
Peptones from fish waste has been widely studied, however information about its shelf life is stilllimited. This study aims to test the storability of dried peptone from tuna and shrimp waste produced through hydrolysis using alcalase enzyme. Peptone powders were packed in HDPE plastic bottles and plastic coated aluminum foil, stored at room temperature, and periodically observed in quality (moisture content, aw, color and appearance). A test was also performed on their ability to support the growth of Staphylococcus aureusbacteria; all were compared to commercial peptone (Difco). Shrimp waste peptone had the highest moisture, ash calcium contents, while tuna peptone has the highest fat content. During five month storage at ambient temperature, all peptones experienced a slight decrease in quality. Aluminum foil performed better than HDPE bottles as a packaging material for peptones, i.e., able to maintain the moisture content, water activity, and appearance. Although the ability to support bacterial growth after five months of storage was slightly affected, the tested peptones were still able to beused as bacterial growing media. It can be concluded that fish waste peptones had comparable quality and shelf-life atambient temperature to commercial peptone.